Prerequisites for the formation of a safe information-educational environment of a modern university - Кыдыралина, Лазат Муктаровна (Ukrainian Information Security Research Journal, 2018)
The paper reviewed and analyzed previous research in the field of protection of the information-educational environment of universities (ILE). It is shown that the priority development of digital education systems in many industrialized countries of the world requires appropriate technical and methodological support of specialists not only in the field of pedagogical activity, but also information technology, taking into account the problems of cyber security and information protection. It is shown that the protected data that is stored and circulate in the information and communication systems of universities, in particular, include: personal data of students, teachers, researchers, support staff; digitized information representing the intellectual property of the educational institution; information arrays that provide the learning process (for example, multimedia content, databases, training programs, etc.); It is substantiated that these information resources can act as an object of theft or distortion from external (internal) computer intruders or from hooliganism, from students or employees. It has been substantiated that the trend towards globalization of access to information resources, formed in many countries, makes relevant the task of introducing the latest digital and information and communication technologies in all areas of activity of a modern university. The relevance of research in the direction of developing models for decision support systems for finding investment management strategies for various ratios of the parameters of the investment process in the cybersecurity systems of educational institutions is substantiated.